Exploring Instructional Leadership Practices at Rantau Kiwa 2 Public Elementary School, Tapin Regency: A Qualitative Case Study - Indah Puspita Sari; Maya Madina; Rilo Pambudi Triantoro; Noor Hairani; Nur Adzkia Kamilah; Putri Medina Heru Arnafama; Suhaimi Suhaimi; Saleh Saleh (FKIP - Universitas Riau, 2026)
This qualitative case study investigates instructional leadership practices at SD Negeri Rantau Kiwa 2, Tapin Regency, based on empirical data from in-depth interviews, participatory observations, and document analysis. The findings reveal that instructional leadership at the school is empirically manifested through four interconnected dimensions: collaborative instructional planning, student-centered and innovative instructional implementation, reflective evaluation grounded in learning outcome data, and systematic follow-up through continuous teacher professional development. Observational and interview data indicate that the principal facilitates structured teacher collaboration, conducts instructional supervision, and utilizes evaluation results to design targeted professional learning activities. The implementation of the Merdeka Curriculum is supported by observable practices, including the integration of digital technology, differentiated instruction, and the establishment of professional learning communities. These findings demonstrate that instructional leadership at SD Negeri Rantau Kiwa 2 operates as a concrete and cyclical set of practices influencing instructional planning, classroom implementation, evaluation, and follow-up within the school context.